The Use of IoT Technology To Support Interactive Learning And The Management of Infrastructure Facilities In Islamic Educational Institutions - Ridha, Ridhatullah Assya'bani; Cahyadi, Ani; Hamdan, Hamdan (The International Journal of Education Management and Sociology, 2025)
This study aims to analyze the use of Internet of Things (IoT) technology in supporting interactive learning and the management of facilities and infrastructure in Islamic educational institutions. The application of IoT in the educational environment is expected to create a more dynamic learning experience, allow teachers and students to interact in real-time, and facilitate efficient supervision and management of school infrastructure. Using a qualitative descriptive type literature methodology, this study examines various relevant literature on the development of IoT in the context of education, especially in Islamic-based educational institutions. The results of the study show that the integration of IoT in the learning management system (LMS) is able to increase student participation and involvement in the learning process, while the management of IoT-connected infrastructure facilities can improve the efficiency of asset monitoring and resource saving. In addition, the use of IoT has the potential to support transparency and accountability in the operational management of educational institutions. This study provides an overview that the application of IoT in Islamic educational institutions opens up new opportunities for innovation in learning and management, which is in line with the needs of education in the digital era.